1991
DOI: 10.1172/jci115292
|View full text |Cite
|
Sign up to set email alerts
|

Study of brain electrolytes and organic osmolytes during correction of chronic hyponatremia. Implications for the pathogenesis of central pontine myelinolysis.

Abstract: Osmotic injury induced by rapid correction of severe chronic hyponatremia has been implicated in the development of central pontine myelinolysis. Organic osmolytes known previously as "idiogenic osmoles" accumulate intracellularly to protect cells from osmotic injury. We investigated the changes of these organic osmolytes as well as electrolytes in the brain during the induction and correction of chronic hyponatremia. Using 'Hnuclear magnetic resonance spectroscopy and HPLC, we found that in rats with chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
0
11

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(141 citation statements)
references
References 32 publications
(60 reference statements)
7
122
0
11
Order By: Relevance
“…The latter is a common clinical condition resulting from volume dysregulation and affects between 2.5-5.0% of hospitalized patients and disproportionately affects the young and the elderly (41,42). Depending on the magnitude, hyponatremia can elicit symptoms ranging from emesis and headaches to respiratory arrest, coma, and brain damage (33).…”
Section: Discussionmentioning
confidence: 99%
“…The latter is a common clinical condition resulting from volume dysregulation and affects between 2.5-5.0% of hospitalized patients and disproportionately affects the young and the elderly (41,42). Depending on the magnitude, hyponatremia can elicit symptoms ranging from emesis and headaches to respiratory arrest, coma, and brain damage (33).…”
Section: Discussionmentioning
confidence: 99%
“…Brunner et al (7) found that the initial severity and duration of the hyponatremia were crucial factors in the development ofpontine lesions. In an animal study, Lien et al (8) reported that a rapid correction of hyponatremia due to Na infusion provokes an overshoot of intracellular Na and Cl levels in brain tissues with decreased ideogenic osmol. MRIhas been shown to be effective to detect disorders such as CPM.…”
Section: Discussionmentioning
confidence: 99%
“…По результатам нашей работы, у мышей опыта через 60 дней после введения СТЗ наблюдается достоверное повышение уровня таурина. Считается, что таурин вместе с креатином и мио-инозитолом участвует в осмотической регуляции мозга (Lien et al, 1990(Lien et al, , 1991. Увеличение уровня таурина отмечается также в головном мозге крыс с СТЗ-индуцированным сахарным диабетом (Rose et al, 2000).…”
Section: физиологическая генетикаunclassified